Ameloblastoma of the Nasal Septum Origin: A Case Report. (21st September 2013) - Temporale, Hanna; Zatoński, Tomasz; Roszkowska, Anna; Kręcicki, Tomasz
Abstract : Background . Ameloblastoma is the most common odontogenic tumor. It represents about 1% of all tumors of the jaw. Extragnathic location of the ameloblastoma is typical and extremely rare. Case Report . We report a case of ameloblastoma of the nasal septum origin, causing nasal obstruction. According to our information, this is the first reported case of ameloblastoma coming from the nasal septum as a primary tumor without maxillary sinus involvement. Conclusions . Ameloblastoma can not only locate in the maxilla and mandible, but also in other regions of the craniofacial. Ameloblastoma should be considered in the differential diagnosis of tumors causing nasal obstruction. Nonspecific clinical features of sinonasal ameloblastoma make it extremely important to perform accurate diagnostic imaging and histopathological examination.